2013
DOI: 10.1504/ijmpt.2013.058973
|View full text |Cite
|
Sign up to set email alerts
|

A micro deep drawing of ARB processed aluminium foil AA1235

Abstract: The flow stress of AA1235 aluminium series-H14 material of 16 to 300 μm thickness has been determined here for the first time which showed the stress reduced significantly with thickness. A stressstrain relationship has been determined as a function of the thickness and grain size. A limiting drawing ratio (LDR) of 2.003 was achieved by a subsequent heat treatment of accumulative roll bonded (ARB) materials before the micro-cup drawing. The cup was successfully formed as the combined process has reduced the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“… and 2 in ref. . Other simplifications were a too small punch diameter d p (100 * g / d p ), above 18 in ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… and 2 in ref. . Other simplifications were a too small punch diameter d p (100 * g / d p ), above 18 in ref.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circular blanks obtained from copper bars processed by conventional equal channel angular pressing (ECAP) were deep‐drawn, and the results demonstrated that the formability of thick UFG disks in biaxial stretching is comparable to the CG material . It has also been proved that a higher limiting drawing ratio (LDR) can be achieved for an ARB‐processed aluminum AA1235 sheet than for its CG counterpart . Since metal‐forming operations can be performed in different complex stress states, these may make it possible to achieve good forming performance even in materials whose ductile properties in the uniaxial strain state are limited, such as UFG metallic materials, but this needs to be carefully investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are characterized by high ductility and low mechanical strength. Although a few authors have investigated the drawability of some special high-strength materials [Had13], these materials are generally difficult to obtain as thin foils with a thickness below 50 µm because cold rolling of high-strength materials is very limited due to strain hardening, which requires a series of multiple cold rolling and annealing processes in order to restore the ductility of these materials after each cold rolling process. Physical vapor deposition (PVD) and particularly magnetron sputtering have been proposed as an alternative process to produce thin foils of high-strength alloys [Sto10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a considerable research effort is made to improve the efficiency and reliability of micro deep drawing and of other micro forming processes [3]. Foil materials employed in micro deep drawing process are quite restricted to a few types of highly available cold rolled foil strips such as pure copper, pure aluminum or austenitic stainless steel [4] although studies were conducted to investigate the drawability of other special materials [5,6].…”
Section: Introductionmentioning
confidence: 99%